ESTUDO GEOFÍSICO DO DISTRITO DE JUÁ MUNICÍPIO DE IRAUÇUBA - CEARÁ, BRASIL - Gonçalves, Francisco Said; Capistrano, Francisco de Assis; Steensma, Gilein; Kellett, Richard; Veríssimo, Liano Silva (Águas Subterrâneas, 2001)
Resumo não disponível.